KARAKTERISASI BIOPLASTIK DARI RUMPUT LAUT (EUCHEUMA COTTONII) DAN PATI SINGKONG DENGAN PENAMBAHAN PATI BIJI ALPUKAT - Gracia Ramadhani Putri (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2019)
The increasing use of plastics in everyday life results in environmental pollution. Synthetic plastic isdifficult to be degraded in nature, so we need the main material for making environmentally friendlyplastics. This research was conducted to synthesize seaweed-based biodegradable plastic (Eucheumacottonii) mixed with cassava starch and polysaccharides derived from various tropical fruit seeds thatare widely available in Indonesia such as avocado and durian with a composition ratio of 3:8:1.Characterization carried out included functional group analysis with FTIR, mechanical properties(tensile strength) and biodegradability.